Performance of small-scale irrigation schemes in Lake Tana Basin of Ethiopia: technical and socio-political attributes. (4th May 2019) - Abera, Abebech; Verhoest, Niko E.C.; Tilahun, Seifu A.; Alamirew, Tena; Adgo, Enyew; Moges, Michael M.; Nyssen, Jan
ABSTRACT: This study was conducted to investigate technical and socio-political attributes that lead to the underperformance of two selected irrigation schemes (Shina and Bebeks) in the Lake Tana floodplains, Ethiopia. Irrigation application efficiency (AE) at nine experimental fields showed a wide range, from 20 to 80%, but was mostly between 40 and 60%. Irrigation water-use efficiency (IWUE) varied from 1.9 to 7.2 kg m −3 for onion and 0.9 to 1.2 kg m −3 for maize. The lined and earthen canal conveyance losses in Bebeks were 0.037 and 0.047 l s −1 m −1, whereas in Shina they were 0.033 and 0.044 l s −1 m −1, respectively. The overall consumed ratio (OCR) of water was 0.58 for Bebeks and varied from 0.73 to 1.2 in Shina. Both schemes are performing below the standard based on technical performance indicators. Irrigation water user associations (WUAs) were not implemented, but irrigation committees (ICs), composed of local political leaders, are managing both schemes. Canal and reservoir sedimentation from erosion of upstream catchment areas during the rainy season was the major problem.